Advances in adsorptive membrane technology for water treatment and resource recovery applications: A critical review. Issue 3 (June 2022) - Adam, Mohd Ridhwan; Othman, Mohd Hafiz Dzarfan; Kurniawan, Tonni Agustiono; Puteh, Mohd Hafiz; Ismail, A.F.; Khongnakorn, Watsa; Rahman, Mukhlis A.; Jaafar, Juhana
Abstract: The presence of recalcitrant contaminants in water bodies such as heavy metals, dyes, pharmaceutical compounds, and chemical residuals results in water pollution. This requires the development of seminal water technologies including adsorptive membrane filtrations. This article critically reviews recent advances in adsorptive membrane technology for wastewater treatment. Particular focus is given on its fabrication and classification, surface characterizations, and their practical applications in removing target pollutants from aqueous solutions. Their advantages and limitations in applications are critically evaluated and compared. Their operational conditions such as pressure, initial pollutant concentration, and treatment performance are presented. Research trends, challenges, solutions, and the way forward for adsorptive membrane filtration are also elaborated. It is conclusively evident from 280 published studies (1971–2022) that integrated adsorption and membrane filtration processes were highly effective in removing refractory pollutants from contaminated wastewater due to their rapid adsorption-desorption rates, low internal diffusion resistance, and high flow rates. The sulfonic groups of the Nafion 117 membrane have a good adsorptive capacity to metal ions such as copper (II), nickel, cobalt, lead and silver ions with their adsorption capacities of 66, 64, 60, 58, and 47 mg/g, respectively. It is important to note that technical applicability, treatment performance, and treatment cost are critical factors in determining the most suitable water technology for treating wastewater laden with recalcitrant contaminants. Further research should address technical bottlenecks such as membrane fouling and agglomeration formation during the adsorptive membrane fabrication and operation. The constraints can be tackled to improve the quality of the membranes fabricated. Graphical Abstract: ga1 Highlights: Conceptual and theoretical aspects of adsorptive membranes for various applications. Dual functional membrane i.e., adsorption and filtration are elaborated. Discussion on alternatives for the conventional powder suspension adsorption process. Bibliometric analysis of adsorptive membranes development is presented. Discussion on the current challenges and future outlooks for adsorptive membranes sustainability.